Does Electronic Word Of Mouth Mediate The Impact Of Product Quality And Brand Image On Smartphone Purchasing Decisions? - Utarini, Ni Kadek Nora; Telagawathi, Ni Luh Wayan Sayang; Widiastini, Ni Made Ary (Relevance: Journal of Management and Business, 2025)
This study investigates the mediating role of electronic word of mouth (e-WOM) in the relationship between product quality, brand image, and smartphone purchasing decisions. A quantitative survey was employed, targeting Samsung smartphone users in Jembrana Regency, Bali Province, Indonesia. Data were collected from 156 respondents through convenience sampling at six major smartphone retail outlets. Structural Equation Modeling was used to analyze the data using the Partial Least Squares (PLS-SEM) method. The results reveal that both product quality and brand image have a significant positive effect on e-WOM. Additionally, product quality was found to have a direct positive influence on purchasing decisions. However, brand image and e-WOM did not show a significant direct effect on purchasing decisions. Furthermore, e-WOM did not mediate the relationship between either product quality or brand image and purchasing decisions. These findings suggest that tangible aspects of product performance influence Samsung users more in this regional market than online reviews or brand perception. The study implies that maintaining high product quality is critical, as it remains the only significant driver of purchase decisions in this context. Future research is recommended to explore the influence of social or cultural factors that may explain the weak impact of e-WOM and brand image on consumer behavior in localized smartphone markets.